2008
DOI: 10.1016/j.rse.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Correction of aerosol effects on multi-temporal images acquired with constant viewing angles: Application to Formosat-2 images

Abstract: This paper presents a new method developed for the atmospheric correction of the images that will be acquired by the Venμs satellite after its launch expected in early 2010. Every two days, the Venμs mission will provide 10 m resolution images of 50 sites, in 12 narrow spectral bands ranging from 415 nm to 910 nm. The sun-synchronous Venμs orbit will have a 2-day repeat cycle, and the images of a given site will always be acquired from the same place, at the same local hour, with constant observation angles. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(70 citation statements)
references
References 19 publications
1
66
0
Order By: Relevance
“…Accuracy in the geolocalization was estimated to about a half-pixel (4 m). The atmospheric correction was performed using the Simplified Method for Atmospheric Correction (SMAC) code [56] with an original method developed for the retrieval of aerosol optical thickness using constant values of atmospheric water vapor and ozone contents [29]. Finally, the Normalized Difference Vegetation Index (NDVI, [57]) was computed as the ratio of the difference between near-infrared and red reflectances from their sum.…”
Section: Formosat-2 Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Accuracy in the geolocalization was estimated to about a half-pixel (4 m). The atmospheric correction was performed using the Simplified Method for Atmospheric Correction (SMAC) code [56] with an original method developed for the retrieval of aerosol optical thickness using constant values of atmospheric water vapor and ozone contents [29]. Finally, the Normalized Difference Vegetation Index (NDVI, [57]) was computed as the ratio of the difference between near-infrared and red reflectances from their sum.…”
Section: Formosat-2 Imagesmentioning
confidence: 99%
“…It is particularly convenient to monitor agricultural areas, which are often made of a juxtaposition of small, more or less homogeneous units (fields) with a high temporal dynamics due to the vegetation phenological cycle (growth and senescence in a few months for annual crops) and agricultural operations (sowing, plowing, irrigation, harvest etc.). The high density of mono-directional FORMOSAT-2 observations has allowed improving image preprocessing (cloud detection and atmospheric correction) and obtaining very accurate time series of surface reflectances and vegetation indices [29]. A few studies have demonstrated the usefulness of time series of FORMOSAT-2 images for the mapping of land cover, the detection of agricultural operations and the monitoring of several key biophysical variables [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the Landsat-8 image is critical to discriminate between summer crops such as corn, potato and sugar beet. Both the SPOT-4 and the Landsat-8 data were calibrated, orthorectified and corrected for the atmosphere (Hagolle et al 2008(Hagolle et al , 2015. The Landsat-8 image was resampled to SPOT-4's resolution and only the first seven spectral bands were kept.…”
Section: Study Area and Datamentioning
confidence: 99%
“…Retrieval using temporal series is becoming increasingly common in operational EO retrieval algorithms for optical and to some extent microwave technologies. Some examples in the optical domain are the correction of aerosol impact for visible images (Hagolle et al, 2008(Hagolle et al, , 2015, cloud detection (Hagolle et al, 2010) and the use of MO for land cover classification (Inglada and Mercier, 2007). The previous methodologies are being implemented for high-end level 2-A and level 3 products for the Copernicus Sentinel-2 mission.…”
Section: Introductionmentioning
confidence: 99%